Subjective and Objective Measures in Assessing Neck Disability and Pain in Head and Neck Cancer. (3rd March 2021) - Magaña, Linda C.; Murati, Sebastian; Riffitts, Michelle; Harrison, Christine; Harris, Alexandria; Sowa, Gwendolyn; Johnson, Jonas T.; Bell, Kevin; Nilsen, Marci
Abstract : Objective/Hypothesis: The intensification of treatment for head and neck cancers (HNCs) has created a cohort of patients living with short‐ and long‐term comorbidities and functional deficits. This study aimed to determine whether there is a relationship between patient‐reported outcomes (PROs) and objective measures of neck function in survivors of HNCs. Study Design: Cross‐sectional study. Methods: Thirty‐one subjects (aged 64 ± 8.7 years; 28 males and three females) were recruited and completed the Neck Disability Index (NDI) and a numeric pain scale. At the same visit, subjects were fitted with two portable motion sensors to collect range of motion (ROM) and velocity data. Differences between ROM, velocity, and PRO subgroups were assessed using a one‐tailed t test (* P  < .05). The Pearson correlation coefficient (r) was calculated between the NDI values and the ROM and velocity values for each motion. Results: A moderate correlation ( r  = 0.507) was observed between NDI and neck pain. Patients with no disability according to the NDI had significantly higher ROM and velocity than patients with mild to moderate disability. Velocity in all degrees of freedom (axial rotation, flexion and extension, and lateral bending) was significantly lower for patients who perceived higher levels of neck pain and neck disability. Conclusions: This study notes that patients who report neck disability and pain have more limited ROM and velocity following HNC treatment. These data may improve treatment planning and care delivery by facilitating an understanding of the experiences of HNC survivors and the pathophysiology that must be targeted to address their psychosocial and functional deficits. Level of Evidence: 4 Laryngoscope, 131:2015–2022, 2021